Asynchronous exposure to global warming: Freshwater resources and terrestrial ecosystems - Gerten, D.; Lucht, W.; Ostberg, S.; Heinke, J.; Kowarsch, M.; Kreft, Holger; Kundzewicz, Z.W.; Rastgooy, J.; Warren, R.; Schellnhuber, H.J. (IOP Publishing, 2013)
This modelling study demonstrates at what level of global mean temperature rise. (∆Tg) regions will be exposed to significant decreases of freshwater availability and changes to terrestrial ecosystems. Projections are based on a new, consistent set of 152 climate scenarios (eight ∆Tg trajectories reaching 1.5–5oC above pre-industrial levels by 2100, each scaled with spatial patterns from 19 general circulation models). The results suggest that already at a ∆Tg of 2oC and mainly in the subtropics, higher water scarcity would occur in >50% out of the 19 climate scenarios. Substantial biogeochemical and vegetation structural changes would also occur at 2oC, but mainly in subpolar and semiarid ecosystems. Other regions would be affected at higher ∆Tg levels, with lower intensity or with lower confidence. In total, mean global warming levels of 2oC, 3.5oC and 5oC are simulated to expose an additional 8%, 11% and 13% of the world population to new or aggravated water scarcity, respectively, with >50% confidence (while~1.3 billion people already live in water-scarce regions). Concurrently, substantial habitat transformations would occur in biogeographic regions that contain 1% (in zones affected at 2oC), 10% (3.5oC) and 74% (5oC) of present endemism-weighted vascular plant species, respectively. The results suggest nonlinear growth of impacts along with 1Tg and highlight regional disparities in impact magnitudes and critical ∆Tg levels.